2012
DOI: 10.1177/1350650112444694
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the influence of surface roughness on the tribological interactions at the shoe–surface interface in tennis

Abstract: The traction provided by shoe-surface interactions in tennis can have an impact on player safety, performance and overall enjoyment of the sport. There is a requirement for an improved scientific understanding of the tribological interactions at the shoe-surface interface and the effects that footwear and surface characteristics have on the traction developed. The aim of this study was to investigate the influence surface roughness has on traction present during a sliding contact between a shoe and an acrylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…The vertical loads ranged from 600 to 1600 N in intervals of 200 N. Three commercially available hard court tennis shoes of the same design but ranging in size (EU sizes 31, 39 and 49) were tested. The shoe-surface contact area of the forefoot segments was calculated using an ink print protocol developed previously (Clarke et al, 2012). Blank paper was rigidly attached onto a smooth acrylic sheet under the shoes before they were loaded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical loads ranged from 600 to 1600 N in intervals of 200 N. Three commercially available hard court tennis shoes of the same design but ranging in size (EU sizes 31, 39 and 49) were tested. The shoe-surface contact area of the forefoot segments was calculated using an ink print protocol developed previously (Clarke et al, 2012). Blank paper was rigidly attached onto a smooth acrylic sheet under the shoes before they were loaded.…”
Section: Methodsmentioning
confidence: 99%
“…The magnitude of these forces in combination with other variables, e.g. surface roughness (Clarke et al 2012) and shoe orientation (Ura et al, 2013) affects the friction generated between the shoe and surface. Previous tennis studies have reported peak vertical forces of 1243.9 ± 99.1 and 1680.5 ± 483.7 N on hard court for a side jump and running forehand movements respectively (Damm et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…the addition of computer-controlled valves allowing a range of dynamic load patterns). A number of studies have used velocity controlled motor-driven mechanical test devices when investigating the traction of shoesurface interactions in sport [35][36][37]. It is argued that velocity-driven traction test devices are not suitable for classifying the traction developed during the initial movement of a shoe relative to a surface.…”
Section: Mechanical Test Device Developmentmentioning
confidence: 99%
“…For example, the execution of a deliberate sliding movement will depend on the dynamic traction developed (Driscoll et al 2012). In tennis an understanding of translational traction for varying shoes, surfaces and loading conditions via mechanical testing has been reported (Clarke et al 2011(Clarke et al , 2012a(Clarke et al , 2012b(Clarke et al , 2013. In tennis, players continuously perform sideways movements yet there is little reported literature to date that examines the influence the shoe orientation has on traction (Driscoll et al 2012).…”
Section: Introductionmentioning
confidence: 99%